WAKTU POTENSIAL APLIKASI MIKORIZA DAN Trichoderma spp. PADA MEDIUM GAMBUT UNTUK MENINGKATKAN PERTUMBUHAN SEMAI MERANTI TEMBAGA (Shorea leprosula Miq.) - Sari, Aulia; Mardhiansyah, M.; Sribudiani, Evi (PEST Tropical Journal, 2014)
Shorea leprosula Miq. is a major timber producing trees and importantcommodity in Indonesia. To get a good quality of Shorea leprosula Miq. shouldbe using proper cultivation techniques. Peat soils potential for growth Shorealeprosula Miq.. Mycorrhiza and Trichoderma spp. can assist the process ofdecomposition of peat soil and improve seedling growth, but need to know thepotential time to apply. This study aims to determine the potential time to applymycorrhizal and Trichoderma spp. in peat medium to boost growth seeds ofShorea leprosula Miq.. This study using a completely randomized design (CRD)consisting of 5 treatments and 10 replications. The treatments used were : T1 =Trichoderma spp. on S-5 and mycorrhiza on S-1, T2 = Trichoderma spp. on S-3and mycorrhiza on S-1, T3 = Trichoderma spp. and mycorrhiza on S-1 , T4 =Trichoderma spp. on S-1 and mycorrhiza on S-3, T5 = Trichoderma spp. on S-1and mycorrhiza on S-5, where S = seedlings were transferred to polybags aftertreatment. Responses were measured to observe the effect of treatments are thesurvival rate of seedlings, seedling height, diameter of the root seedling, plant dryweight and the ratio of crown/root. The results obtained from this study indicatedthat the time of application of Trichoderma spp. at 1 (one) day prior to weaningand mycorrhiza on three (3) days prior to weaning tended to show better results onShorea leprosula Miq. seedling growth.Keywords: Shorea leprosula Miq., Trichoderma spp., Mycorrhizal, peat medium